ChemInform Abstract: Synthesis and Tautomerism of Substituted Pyrazolo[4, 3‐c]pyrazoles. Issue 10 (11th March 2014) - Kadam, Shivaji S.; Maier, Lukas; Kostakis, Ioannis; Pouli, Nicole; Tousek, Jaromir; Necas, Marek; Marakos, Panagiotis; Marek, Radek
Abstract The spectroscopic data for all isomers [(III)‐(V)] and [(VII)‐(IX)] are interpreted by DFT methods.